The feoABC Locus of Yersinia pestis Likely Has Two Promoters Causing Unique Iron Regulation - O'Connor, Lauren; Fetherston, Jacqueline D.; Perry, Robert D. (Frontiers in Cellular and Infection Microbiology, 2017)
The FeoABC ferrous transporter is a wide-spread bacterial system. While the feoABC locus is regulated by a number of factors in the bacteria studied, we have previously found that regulation of feoABC in Yersinia pestis appears to be unique. None of the non-iron responsive transcriptional regulators that control expression of feoABC in other bacteria do so in Y. pestis. Another unique factor is the iron and Fur regulation of the Y. pestis feoABC locus occurs during microaerobic but not aerobic growth. Here we show that this unique iron-regulation is not due to a unique aspect of the Y. pestis Fur protein but to DNA sequences that regulate transcription. We have used truncations, alterations and deletions of the feoA::lacZ reporter to assess the mechanism behind the failure of iron to repress transcription under aerobic conditions. These studies plus EMSAs and DNA sequence analysis have lead to our proposal that the feoABC locus has two promoters: an upstream P1 promoter whose expression is relatively iron-independent but repressed under microaerobic conditions and the known downstream Fur-regulated P2 promoter. In addition, we have identified two regions that bind Y. pestis protein(s), although we have not identified these protein(s) or their function. Finally we used iron uptake assays to demonstrate that both FeoABC and YfeABCD transport ferrous iron in an energy-dependent manner and also use ferric iron as a substrate for uptake.